2022
DOI: 10.3389/fpls.2022.872218
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequence Analysis of the Defense Responses of Resistant and Susceptible Cucumber Strains to Podosphaera xanthii

Abstract: Powdery mildew (PM) caused by Podosphaera xanthii poses a continuous threat to the performance and yield of the cucumber (Cucumis sativus L.). Control in the initial stages of infection is particularly important. Here, we studied the differential physiological and transcriptomic changes between PM-resistant strain B21-a-2-1-2 and PM-susceptible strain B21-a-2-2-2 at the early stage of P. xanthii attack. When challenged with P. xanthii, the tolerant line can postpone the formation of the pathogen primary germ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…It is noteworthy that this finding resonates with previous transcriptomic explorations conducted with cucumber, watermelon, and tobacco. These antecedent investigations similarly unveiled that resistant strains tend to manifest an enhanced DEG expression profile when juxtaposed with their susceptible counterparts during the ordeal of biotic stress [ 33 , 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that this finding resonates with previous transcriptomic explorations conducted with cucumber, watermelon, and tobacco. These antecedent investigations similarly unveiled that resistant strains tend to manifest an enhanced DEG expression profile when juxtaposed with their susceptible counterparts during the ordeal of biotic stress [ 33 , 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This investigative avenue has extended to encompass the defensive responses of mango against Colletotrichum gloeosporioides [ 31 ], tomato against Phytophthora parasitica [ 32 ], and tobacco against Phytophthora nicotianae [ 33 ]. Contemporary focus has converged on transcriptomic inquiries targeting cucurbit species such as cucumber, watermelon, and melon—deciphering their inherent resilience to PM [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…WRKY3/4, WRKY18, WRKY22/29, WRKY33, WRKY38/62, WRKY46/53/70, and WRKY8/28/48 have been reported to regulate the SA-triggered defense process in Arabidopsis thaliana (Asai et al 2002 ; Wang et al 2006 ; Zheng et al 2006 ; Eulgem and Somssich 2007 ; Kim et al 2008 ; Xing et al 2008 ; Pandey and Somssich 2009 ; Spoel et al 2009 ; Hu et al 2012 ; Jiang et al 2017 ). In cucumber, WRKYs were reported participating in regulating its resistance to biotic and abiotic stresses (Chen et al 2020 ; Yang et al 2020 ; Meng et al 2022 ). ABA mediates the cold response of cucumber via regulating the CsWRKY41/CsWRKY46-miR396b-5p-CsTPR module (Sun et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al reported the mining of five DR genes via the inoculation of a rice near-isogenic line of NLS- bls2 after inoculation with a wild-type Xoc strain and a TALE-knockout Xoc strain, which conferred compatible and incompatible interactions, respectively, on rice [ 21 ]. Meng et al identified potential disease resistance genes by comparing the transcriptomes of powdery mildew-resistant and powdery mildew-susceptible cucumber materials [ 22 ]. Cao et al identified 388 potential key DR genes for banded leaf and sheath blight (BLSB) resistance by analyzing the transcriptomes of maize plants infected with a hypovirulent strain or a hypervirulent strain of Rhizoctonia solani for 3 or 5 days via transcriptomic deep sequencing [ 23 ].…”
Section: Introductionmentioning
confidence: 99%